The Quran = [Qurʼān majīd] : the eternal revelation vouchsafed to Muhammad, the Seal of the Prophets - Khan, Muhammad Zafrulla, 1893-1985 (Curzon Press, 1981)
Combines Arabic scholarship and Islamic learning into English translation, while remaining true to the meaning of the text. The Arabic text and the English translation are printed side-by-side to allow for comparison